Effects of shielding gas composition on the welding stability, microstructure and mechanical properties in laser-arc hybrid welding of high nitrogen steel. (10th August 2018) - Bo, Cui; Hong, Zhang; Fengde, Liu
Abstract: This paper deals with laser-arc hybrid welding of high nitrogen stainless steel (HNS) with 1.2 mm diameter of austenitic stainless steel (ASS) filler wire. The welding was carried out with different shielding gas mixtures like 100%Ar, 95%Ar + 5%N2, 90%Ar + 10%N2, 94%Ar + 5%N2  + 1%O2 and 89%Ar + 10%N2  + 1%O2 . The effects of shielding gas composition on the welding stability, microstructure and mechanical properties were analyzed. The results show that the weld seam forming and welding stability are improved when 1%O2 is added to the mixture of Ar + N2, and the nitrogen content in the weld increases significantly. The pore ratio is the lowest in 90%Ar + 10%N2 shielded weld, when 1%O2 is added to 90%Ar + 10%N2, the pore ratio increases slightly. The ferrite percentage is the lowest in 89%Ar + 10%N2  + 1%O2 shielded weld. The 89%Ar + 10%N2  + 1%O2 shielded welded joints feature better mechanical properties.